Molecular Dynamics Simulation Study of Eucommiaulmoides GUM/AG Nanoparticle Composites. Issue 4 (July 2017) - Li, Fei-Zhou; Lu, Zhen-Lin; Xi, Yuntao; Wang, Xin-sheng; Zhu, Ming-qiang
A study of eucommia ulmoides gum (EUG)/Ag nanoparticle (NP) composites by molecular dynamics (MD) simulations to understand their structure, polarizability, thermodynamic properties, and mechanical properties is proposed. The effects of simulation temperature and Ag NPs size on these parameters were also studied. The results revealed that the composites exhibited an isotropic amorphous structure, and the distribution uniformity of the Ag NPs was enhanced by changing the simulation temperature. Several atoms of the Ag NPs were in an amorphous state, and a polarized layer was observed on the interface between the Ag NPs and the eucommia ulmoide matrix. The interface size increased as the temperature increased and nanoparticles size decreased. The isochoric heat capacity and thermal pressure coefficient of the EUG/Ag-NP composites exhibited significant size effects and improved thermal interferences, which indicated that the presence of the Ag NPs had a positive effect on the mechanical properties of the EUG.